Treatment of Neonatal Tetanus with High Dosage Diazepam - Tjut Dharmawati; Fauzi Rizal; Munar Lubis; Chairul Yoel; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 1993)
A retrospective study on neonatal tetanus, among patients hospitalized at the pediatric ward of Dr. Pirngadi Hospital Medan, bad been conducted from january 1987 through December 1991. There were 75 cases out of 13,581 patients hospitalized (0.55%) in that period, consisting of 44 boys (58.66%) and31 girls (47 3 %) with an overall case fatality rate of 33.33%. Of 18 patients with an incubation period of 5 days or less, 12 (66.66%) died, while of 4 patients with an incubation period of more than 10 days, there were not any death at all. Diazepam had been given in a dosage of 10-40 mg/kg body weight/day . Diazepam of 10-19 mg/kg body weight/day was given to 4 cases, and the case fatality rate was 25% . Of 42 cases treated with diazepam of 30-40 mg/kg body weight/day, the case fatality rate was 42.85% The duration of hospitalization varied between ten hours to 34 days. All deaths (25 cases) occurred within the first seven days of hospitaltization. The most common accompanying disease was bronchopneumonia (6 cases). Endotracheal intubation were performed on 11 cases, while the mechanical ventilator in 1 case with a case fataliy rate of 27,27% and 0% respectively.